2005
DOI: 10.1523/jneurosci.2110-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of KCNQ4 in Inner Hair Cells and Sensory Neurons Is the Basis of Progressive High-Frequency Hearing Loss

Abstract: Human KCNQ4 mutations known as DFNA2 cause non-syndromic, autosomal-dominant, progressive high-frequency hearing loss in which the cellular and molecular basis is unclear. We provide immunofluorescence data showing that Kcnq4 expression in the adult cochlea has both longitudinal (base to apex) and radial (inner to outer hair cells) gradients. The most intense labeling is in outer hair cells at the apex and in inner hair cells as well as spiral ganglion neurons at the base. Spatiotemporal expression studies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 51 publications
13
111
2
Order By: Relevance
“…Similar expression patterns have been noted for KCNQ4 (Beisel et al, 2005) and prestin (Judice et al, 2002;Zheng et al, 2002) in cochlear hair cells, which suggests that the turnover rate may be slower for some hair-cell proteins than the corresponding mRNA turnover rate. Four alternative splice variants of KCNQ4 have been identified previously in tissue harvested from mouse cochleas and vestibular organs (Beisel et al, 2005;Rocha-Sanchez et al, 2007). Three splice forms result from the alternate use of exons 9 through 11, and the fourth lacks all three exons.…”
Section: Expression Of Kcnq4 Mrna In the Mouse Utriclesupporting
confidence: 68%
See 3 more Smart Citations
“…Similar expression patterns have been noted for KCNQ4 (Beisel et al, 2005) and prestin (Judice et al, 2002;Zheng et al, 2002) in cochlear hair cells, which suggests that the turnover rate may be slower for some hair-cell proteins than the corresponding mRNA turnover rate. Four alternative splice variants of KCNQ4 have been identified previously in tissue harvested from mouse cochleas and vestibular organs (Beisel et al, 2005;Rocha-Sanchez et al, 2007). Three splice forms result from the alternate use of exons 9 through 11, and the fourth lacks all three exons.…”
Section: Expression Of Kcnq4 Mrna In the Mouse Utriclesupporting
confidence: 68%
“…Furthermore, Beisel et al (2000Beisel et al ( , 2005 have noted a temporal correlation between the physiological expression of G K,n and the molecular expression of KCNQ4, both following an apical to basal expression pattern. Previously, Kharkovets et al (2006) also showed a lack of G K,n expression in KCNQ4 knock-out mice.…”
Section: Molecular Expression Of Kcnq4 In Cochlear Hair Cellsmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, the same study revealed that some Kv channels, such as K Ca , Kv3.1, and Kv1.1 subunits, were distributed predominantly in the basal SGNs and Kv4.2 predominantly in the apical SGNs (36). Later studies revealed other channels, such as Kv7.4 (25,47), also demonstrate an expression gradient along the cochlear axis. Therefore, specialized electrophysiological signatures along the cochlear axis are governed by differential ion channel distributions in the cochleae.…”
Section: Discussionmentioning
confidence: 90%